PERAN ORANG TUA DALAM MENGOPTIMALISASI KETERGANTUNGAN ANAK PADA SMARTPHONE - ana cahayani fatimah (Prodi PAI STIT Sunan Giri Bima, 2022)
This study aims to analyze the shape of the role of parents in optimizing children's dependence on smartphones in the Bima area in particular. The form of smartphone use in children can be classified at high, medium, and low levels. Low category if the use of smartphones is only during free time for example when coming home from school or after studying and the duration of use is only half an hour. Medium category is if smartphone usage ranges from 40 to 60 minutes in one use 2 to 3 times per day. However, if the use of smartphones has a duration of more than 60 minutes per day continuously or more than 120 minutes in one use, it can be categorized as a high level of smartphone use and can be said to have an attitude of dependence. The data collection techniques used are: (1) observation; (2) interviews; (3) documentation. Research results In carrying out its role in optimizing smartphone dependence experienced by their children, parents have their own way and the impact of smartphone dependence experienced by children in the Bima area, namely, disrupting sleep patterns, disrupting the learning process and the impact financially or economically. If this is allowed to continue, this will have a serious impact on children in the future, children will tend to be more concerned with smartphones than other more important things. In addition, the child will become a lazy person and it will affect the success of his life in the future.